Stress-strain behavior and model of bamboo scrimber under cyclic axial compression. (15th April 2020) - Wei, Yang; Tang, Shuaifeng; Ji, Xuewei; Zhao, Kang; Li, Guofen
Highlights: Bamboo scrimber were tested under cyclic compression loading. Cyclic compressive behavior of bamboo scrimber was investigated for the first time. Bamboo scrimber has prominent flexibility and recovery performance. Cyclic stress-strain model is developed for predicting the entire cyclic stress-strain response. Abstract: Bamboo has become a promising construction material for replacing nonrenewable and polluting materials due to its ecological characteristics, low carbon content, high axial strength, favorable flexibility, and associated energy savings. Although the excellent flexibility and recovery abilities of bamboo have been recognized, their quantitative description has not yet been established. To quantitatively describe the flexibility and recovery performance of bamboo, the compressive behavior of bamboo scrimber columns under cyclic compressive loading was investigated for the first time. The results illustrate that the failure modes of bamboo scrimber columns include buckling, shearing and splitting, and the residual plastic strain ratio of bamboo scrimber is far lower than that of concrete in a high strain range. A cyclic stress-strain model, including the envelope and the unloading and reloading segments of the cyclic stress-strain curve, was developed for predicting the entire cyclic stress-strain response of bamboo scrimber. The proposed model is able to accurately predict the entire cyclic stress-strain response of bamboo scrimber and provides a quantitative description of the flexibility and recovery abilities of bamboo, which can be used to simulate the seismic response of bamboo structures.